Development of Eye Care Android Application for Children - ali, azita; Zainudin , Nur Fatin Syuhadah (Research and Innovation in Technical and Vocational Education and Training, 2021)
Abstract: The study was conducted to develop an eye care app for children to convey information and to alert parents or guardians about the importance of keeping an eye on children using the android application platform. The issue of eye care among children has been ignored because many children have vision problems early in their age. The development of this android application is very interesting and suited to the present-day delivery method of this technology which can be translated into a more dynamic form than the use of statistically-presented information delivery using the right distance to the smartphone screen. Waterfall models serve as a guide throughout the process of developing this application. The testing and evaluation of this application is done through expert review methods that have been performed on four experts. In this study, three interface experts were selected, lecturers with extensive skills in creative multimedia from the Faculty of Technical and Vocational Education, University of Tun Hussein Onn Malaysia (UTHM) and an expert in eye-catching content from the Islamic University of Malaysia (USIM). The results of the study show that all experts have given positive comments, suggestions and feedback on this developed application. In conclusion, this app can alert parents or guardians of the importance of keeping an eye on children. It is hoped that this app will become an interactive health knowledge platform and will attract more parents or guardians to provide good care for the child's eyes. Keywords: Eye Care Application, Children, Eye Exercises